2021
DOI: 10.1111/ele.13736
|View full text |Cite
|
Sign up to set email alerts
|

Interaction diversity explains the maintenance of phytochemical diversity

Abstract: The production of complex mixtures of secondary metabolites is a ubiquitous feature of plants. Several evolutionary hypotheses seek to explain how phytochemical diversity is maintained, including the synergy hypothesis, the interaction diversity hypothesis, and the screening hypothesis. We experimentally tested a set of predictions derived from these hypotheses by manipulating the richness and structural diversity of phenolic metabolites in the diets of eight plant consumers. Across 3940 total bioassays, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(104 citation statements)
references
References 47 publications
3
93
0
Order By: Relevance
“…The overwhelming majority of synergy tests to date have used artificial diets (e.g. Whitehead et al 2021), and non-metabolite defenses like (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
“…The overwhelming majority of synergy tests to date have used artificial diets (e.g. Whitehead et al 2021), and non-metabolite defenses like (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
“…This is a different mechanism than, for example, a diverse mixture providing a more effective defense against any single antagonist due to compound synergies (the synergy hypothesis, Box 1), or providing a more specific odor blend that can attract a specific mutualist (the specific communication hypothesis, Box 1), and leads to different predictions. Individual plants that have more unique defensive compounds in fruits may not be better defended against any single seed predator, but they will be better defended against a complex community of seed predators, pathogens, and other antagonists and ultimately have higher fitness than neighboring plants with low fruit chemical diversity (Whitehead et al 2021). For classes of compounds that function to increase the effectiveness of mutualistic interactions (e.g.…”
Section: Effects Of Fruit Phytochemical Composition and Diversity On Fruit-frugivore Interactionsmentioning
confidence: 99%
“…Diverse mixtures are more biologically active because of greater than additive effects of secondary metabolites when they occur in mixtures. Evidence suggests that synergies among compounds are common (reviewed by Richards et al 2016); however, it is still unclear whether the probability of beneficial synergies increases with the diversity of a mixture, providing a selective advantage for phytochemically diverse plants (Whitehead et al 2021). • Slowed adaptation hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, targeted metabolomics approaches revealed that total phenolic concentrations in birch Betula pendula leaves increased with plot diversity level (Poeydebat et al, 2020). Different phenolic compounds, however, can have very different effects on herbivores and pathogens (Whitehead et al, 2021). Untargeted metabolomics can provide more detail on the identity and composition particular phenolics, as well as on the presence of other compound classes, such as alkaloids, which play important roles in ecological interactions (Peters et al, 2018).…”
Section: Synthesismentioning
confidence: 99%